Direct and host-mediated interactions between Fusarium pathogens and herbivorous arthropods in cereals - Drakulic, Jassy; Bruce, Toby; Ray, Rumiana V. (Wiley, 2017)
Fusarium head blight and fusarium ear rot diseases of cereal crops are significant global problems, causing yield and grain quality losses and accumulation of harmful mycotoxins. Safety limits have been set by the European Commission for several Fusarium-produced mycotoxins; mitigating the risk of breaching these limits is of great importance to crop producers as part of an integrated approach to disease management. This review examines current knowledge regarding the role of arthropods in disease epidemiology. In the field, diseased host plants are likely to interact with arthropods that may substantially impact the disease by influencing spread or condition of the shared host. For example, disease progress by Fusarium graminearum can be doubled if wheat plants are aphid-infested. Arthropods have been implicated in disease epidemiology in several cases and the evidence ranges from observed correlations between arthropod infestation and increased disease severity and mycotoxin accumulation, to experimental evidence for arthropod infestation causing heightened pathogen prevalence in hosts. Fusarium pathogens differ in spore production and impact on host volatile chemistry, which influences their suitability for arthropod dispersal. Herbivores may allow secondary fungal infection after wounding a plant or they may alter host susceptibility by inducing changes in plant defence pathways. Post-harvest, during storage, arthropods may also interact with Fusarium pathogens, with instances of fungivory and altered behaviour by arthropods towards volatile chemicals from infected grain. Host-mediated indirect pathogen–arthropod interactions are discussed alongside a comprehensive review of evidence for direct interactions where arthropods act as vectors for inoculum.